MOŻLIWOŚĆ KONSTRUOWANIA OGÓLNEJ TEORII ZASAD PRAWA UWAGI DO KONCEPCJI ROBERTA ALEXY’EGO - Kordela, Marzena (Wydział Prawa i Administracji UAM, 2007)
Since the middle eighties o f the 20th century Robert Alexy has consistently developed the conception of legal principles. That conception, despite its initial ancillary function in respect of the theory of constitutional rights that he worked on, very soon proved of major importance as its basic theses applied to all norms o f conduct which belong to a legal system and have been defined as principles. There two types o f factors that have decided about the universal nature of this conception. They are (1) the approach that looks at legal principles as optimisation commands which formulate an obligation to carry out a certain state o f affairs to the highest degree in the existing actual and legal circumstances, and (2) the procedure of balancing the principles, which is a formalised expression of solving of the, inevitable in the system, collision o f principles. Although Alexy has not as yet articulated clearly that a general, not only a particular, theory of principles could be built on the basis o f his work so far, it seems justified to believe, having in mind the advanced stage of the already existing conception, and, what is more, its practical usability in areas beyond constitutional law, that sound foundations on which this conception could be grounded already exist.
THE POSSIBILITY OF CONSTRUCTING THE GENERAL THEORY OF LEGAL PRINCIPLES. REMARKS ON ROBERT ALEXY’S CONCEPTION